“Perempuan Asing” Dalam Amsal 2:16, 5:20, 6:24, 7:5 Dan 23:27 - Aska Aprilano Pattinaja; Farel Yosua Sualang (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This phrase "strange woman" appears several times in the Book of Proverbs and is problematic. Some translate it as a seductress, a bitch, a woman who has an affair, and as a wicked woman. Interestingly, all these interpretations of the phrase have negative connotations in the context. If so, why is this phrase always associated with negativity? What is the true meaning of this phrase? There seems to be a research gap in discussing this phrase, which is the main reason for the author to provide a specific and comprehensive interpretation of the phrase "foreign woman" and its implications for women today. Based on the qualitative method with sub interpretative design, especially wisdom literature hermeneutics, this study found that, there are five important meanings that explain the phrase "strange woman," namely, a woman who is unfaithful to the covenant with God, a woman who does not honor marriage, a harlot, a seductress, and a wicked woman. The implication of this study is a reference and warning for women to build the right character and become wise women so that they can be exemplary as good mothers and wives.